Modern methodology for the development of parametric models for determining the cost of transporting freights for tariff setting purposes - E. N. Efimova; P. B. Manevich; A. V. Shmelev (Вестник Научно-исследовательского института железнодорожного транспорта)
One of the key problems of organizing an effective The article considers problems of the influence of technical transportation process is an adequate reflection of the current and technological parameters of freight transportation by rail on pricing factors in the tariff system. This can be done on the basis of the cost price for tariff purposes, the distribution of the cost of the the development of appropriate models for determining the cost initial-final operation between loaded and empty cars, determinaof transportation. Modeling the cost of transporting freights by rail tion of coefficients taking into account the length of cars and the for tariff purposes is based on determining and assessing the rela-distance of transportation, as well as the methodology for the distionship between transportation costs and work indexes. tribution of costs between the initial-final and motion operations. Proposed updated methodology for constructing parametric models for determining the cost of transportation of freights for tariff setting purposes includes: method of itemized distribution of expenditures between non-commercial organizations and affiliated subsidiaries in terms of infrastructure and traction; procedure for allocating the costs, attributed to affiliated subsidiaries, to the indexes “ton-kilometer gross” and “car-kilometer”; system of itemized distribution of freight costs for the indexes of the transportation operation, as well as the system for calculating the aggregate expenditure rates (AER) used in parametric models of the cost price; actualized assessment of the influence of the length of the car on the cost value for tariff setting purposes; procedure for allocating the cost of initial-final operations between loaded and empty cars. The developed parametric models for calculating the cost of transportation for tariff purposes for transportation by the locomotive of the JSC “Russian Railways” take into account such factors as the distance of transportation, the weight of the container and the length of the car, its loading, the type of shipment. Within the framework of creating new parametric models, the following factors have been updated: coefficients that take into account the length of the car; coefficients that take into account the effect on the cost of production up to the distance of transportation in connection with the change in the relative distance of carriage of the car as part of mixed and transfer-and-export trains; coefficients depending on the type of shipment.